Pre-existing Immunity to Japanese Encephalitis Virus Alters CD4 T Cell Responses to Zika Virus Inactivated Vaccine - Lima, Noemia S.; Moon, Damee; Darko, Samuel; De La Barrera, Rafael A.; Lin, Leyi; Koren, Michael A.; Jarman, Richard G.; Eckels, Kenneth H.; Thomas, Stephen J.; Michael, Nelson L.; Modjarrad, Kayvon; Douek, Daniel C.; et al. (Frontiers in Immunology, 2021)
The epidemic spread of Zika virus (ZIKV), associated with devastating neurologic syndromes, has driven the development of multiple ZIKV vaccines candidates. An effective vaccine should induce ZIKV-specific T cell responses, which are shown to improve the establishment of humoral immunity and contribute to viral clearance. Here we investigated how previous immunization against Japanese encephalitis virus (JEV) and yellow fever virus (YFV) influences T cell responses elicited by a Zika purified-inactivated virus (ZPIV) vaccine. We demonstrate that three doses of ZPIV vaccine elicited robust CD4 T cell responses to ZIKV structural proteins, while ZIKV-specific CD4 T cells in pre-immunized individuals with JEV vaccine, but not YFV vaccine, were more durable and directed predominantly toward conserved epitopes, which elicited Th1 and Th2 cytokine production. In addition, T cell receptor repertoire analysis revealed preferential expansion of cross-reactive clonotypes between JEV and ZIKV, suggesting that pre-existing immunity against JEV may prime the establishment of stronger CD4 T cell responses to ZPIV vaccination. These CD4 T cell responses correlated with titers of ZIKV-neutralizing antibodies in the JEV pre-vaccinated group, but not in flavivirus-naïve or YFV pre-vaccinated individuals, suggesting a stronger contribution of CD4 T cells in the generation of neutralizing antibodies in the context of JEV-ZIKV cross-reactivity.